Problems and solutions on mechanics - Yung-kou, Lim; The Physics Coaching Class University of Science and Technology of China (Singapore: World Scientific, 1994)
The material for these volumes has been selected from the past twenty years' examination questions for graduate students at the University of California (Berkeley), Columbia University, the University of Chicago, MIT, State University of New York at Buffalo, Princeton University and the University of Wisconsin.
Index 751-757p
Keywords: Mechanics; Physics